ANALISIS PERAN DAN EFEKTIVITAS HUKUM DALAM MELAWAN ANCAMAN CYBERCRIME DI INDONESIA - Fahmi, Muhammad Hisyam; Henri Marusaha Tambunan (LPPM Universitas Nias Raya, 2024)
This article discusses the challenges faced and the role of law in dealing with the threat of cybercrime in Indonesia amidst the rapid progress of digital technology. The main focus of this article is on the Information and Electronic Transactions Law (UU ITE) as the main legal framework, and the role of the National Cyber ​​and Crypto Agency (BSSN) in coordinating and dealing with cyber threats. In addition, this article identifies several crucial challenges such as technical limitations, rapid technological developments, and digital anonymity of cybercriminals. Evaluation of the effectiveness of regulations and personal data protection is also the focus of this discussion, while providing recommendations for strengthening technological infrastructure, increasing training, strengthening international cooperation, and revising existing regulations to be able to face increasingly complex threats in today's digital era.